Pengembangan E-Book Berbasis Android dengan Soal HOTS untuk Membantu Menganalisis Besaran Pada Materi Gerak Lurus - Wahyudha Tri Setiyoaji; Edi Supriana; Yoyok Adisetio Laksono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
The integration between interactive media and HOTS question could give a big impact on learning process in class room, especially on learning interest and student concept understanding. Android is a learning media that could save more information and questions like ebook. This study was conducted to determine the feasibility of an Android-based electronic book with High Order Thinking Skills to Help Students Analyze Amounts on Straight Motion Material. This research method was used in the ADDIE model (analysis, design, development, implementation, and evaluation). The electronic book was tested for validation by the validator with an average value of 3.94 and the module readability test with respondents of 25 students who obtained an average value of 96%. Based on the data obtained, it can be conclude that the electronic book has decent criteria.